MOBAQ-LUX8 – ELABORATION OF COMPETENCE-ORIENTED TEST ITEMS FOR 8YEAR-OLD LUXEMBOURGISH STUDENTS (Fiep Bulletin - online, 2014)
The University of Luxembourg conducts the project of Basic Motor Qualifications (MOB AQ) in order to gather more information on the motor status and potential deficiencies of young students at the age of 8 years. The MOB AQ-concept is an innovative competence oriented concept to evaluate basic motor qualifications of students permitting PE teachers to foster students individually. The first step of the project is to elaborate competence-oriented test items according to the MOB AQ-approach (Kurz & Fritz, 2007) and according to quality criteria of standardized tests. A next step is to use the test battery in a project phase to establish a diagnosis for pedagogical purposes in several school classes of the class level 3 in elementary school in Luxembourg. In opposition to usual approaches based on abilities and the statistical legitimating of minimal standards, the MOB AQ-approach fixes normatively basic motor qualifications as minimal requirements for students to be able to participate in the movement culture. In accordance to the MOB AQ-approach, a basic motor qualification can be described as a motor task that (1) is sufficiently complex; (2) is related to a specific context or domain, and (3) can be codified in a binary way. First, MOB AQ-test-items in accordance to classical test-criteria will be developed. Secondly, results of the use of MOB AQ-testbatteries will deliver results about the basic motor qualifications of Luxembourgish students and their background.
Keywords: motor qualifications; competence orientation; motor test; test validation